Square root problem for divergence operators and related topics - Auscher Pascal; Tchamitchian Philippe (Paris Societe Mathematique de France, 1998)
This volume contains recent progress on the square root problem of Kato for differential operators in divergence form on R to the power n. It discuss topics on functional calculus, heat and resolvent kernel estimates, square function estimates and Carles
Keywords: Differential operators; Square root problem